1991
DOI: 10.1177/026765919100600311
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-coating of extracorporea circuits reduces thrombin formation in patients undergoing cardiopulmonary bypass

Abstract: This clinical study was performed to evaluate the inhibiting effects of heparincoated extracorporeal circuits on thrombin formation during cardiopulmonary bypass (CPB). Thirty patients undergoing coronary artery bypass grafting were randomly divided into two groups with (Duraflo II, n =15) orwithout (control, n =15) the use of heparin-coated circuits. Standard systemic heparinization was performed in all the patients before CPB. The results showed that thrombin formation during the first phase of CPB was inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Despite these improvements, however, we and also other investigators reported no reduction in thrombin generation in patients undergoing CPB with the use of a heparin-coated extracorporeal circuit [14-17], whereas others have found evidence of some possible benefit of these surfaces on the coagulation cascade [18]. …”
Section: Introductionmentioning
confidence: 63%
“…Despite these improvements, however, we and also other investigators reported no reduction in thrombin generation in patients undergoing CPB with the use of a heparin-coated extracorporeal circuit [14-17], whereas others have found evidence of some possible benefit of these surfaces on the coagulation cascade [18]. …”
Section: Introductionmentioning
confidence: 63%
“…Based on current experimental and clinical data, we believe that HBCs with lower levels of anticoagulation are more thromboresistant than conventional (nonheparin bonded) circuit with full anticoagulation. [17][18][19][20] As with all modifications, the techniques of CPB have to be adjusted to ensure patient safety and the limitations of these techniques have to be clearly understood.13 These limitations are not unique to HBCs, but are shared by all extracorporeal circulation modalities, although concerns are accentuated in the presence of lower anticoagulation. These concerns include identification with patients with hypercoagulable states or antithrombin Ill deficiencies, intraoperative administration of any drugs which shift the hemostatic balance and promote thrombosis, and avoidance of blood turbulence and stagnation.…”
Section: Resultsmentioning
confidence: 99%
“…17 The blood-surface interface changes when heparinbonded circuits are used during CPB, resulting in reduced activation of neutrophils, platelets, and complement. [18][19][20][21][22][23][24] Heparin can be bonded either ionically or covalently to plastic surfaces due to its strong acidity.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant difference resulting from the two types of bonds appears to be that the weaker ionic bonds result in leaching and higher post-CPB heparin levels. 20,25 …”
Section: Introductionmentioning
confidence: 99%